2020
DOI: 10.1126/science.abc9546
|View full text |Cite
|
Sign up to set email alerts
|

A ubiquitin ligase mediates target-directed microRNA decay independently of tailing and trimming

Abstract: MicroRNAs (miRNAs) act in concert with Argonaute (AGO) proteins to repress target mRNAs. After AGO loading, miRNAs generally exhibit slow turnover. An important exception occurs when miRNAs encounter highly complementary targets, which can trigger a process termed target-directed microRNA degradation (TDMD). During TDMD, miRNAs undergo tailing and trimming, suggesting that this is an important step in the decay mechanism. Here, we identified a cullin-RING ubiquitin ligase (CRL), containing the substrate adapte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
211
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(244 citation statements)
references
References 46 publications
11
211
1
2
Order By: Relevance
“…This is consistent with recent kinetic analysis which demonstrated that tailing is faster than 3’ trimming, so miRNAs are more likely to carry a tail as they age (8). TDMD is the most frequently-studied context in which tailing correlates with decay, yet recent work on TDMD suggests that tailing is correlative – not causative – of TDMD, and that conformational changes that promote decay of the Argonaute-miRNA complex also expose the miRNA 3’ end to TENTs (27, 28, 30, 31). However, in specific developmental contexts, tailing does promote wholesale miRNA turnover (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with recent kinetic analysis which demonstrated that tailing is faster than 3’ trimming, so miRNAs are more likely to carry a tail as they age (8). TDMD is the most frequently-studied context in which tailing correlates with decay, yet recent work on TDMD suggests that tailing is correlative – not causative – of TDMD, and that conformational changes that promote decay of the Argonaute-miRNA complex also expose the miRNA 3’ end to TENTs (27, 28, 30, 31). However, in specific developmental contexts, tailing does promote wholesale miRNA turnover (32).…”
Section: Discussionmentioning
confidence: 99%
“…This process, known as target-directed miRNA degradation (TDMD), is induced by a handful of known naturally-occurring triggers, including tissue-specific lncRNAs and viral small RNAs that target a host miRNA (20)(21)(22)(23)(24)(25). While tailing was initially assumed to be causative of miRNA decay in this context, recent studies demonstrate examples in which tailing is dispensable for TDMD, suggesting that 3' tailing may be a symptom of miRNA 3' end display rather than an upstream regulatory event in TDMD (25)(26)(27)(28)(29).…”
mentioning
confidence: 99%
“…43 Knocking out this conserved section of exon 3 in mice showed miR-7 upregulation in brain tissue. 37 Moreover, two independent groups recently reported that the ZSWIM8 Cullin-RING ligase mediates miR-7 degradation caused by Cyrano in a human cell line, 44,45 which indicates that Cyrano/ miR-7 regulation exists in multiple cellular contexts. These studies of Cyrano collectively indicate the challenges on dissecting the function of lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, more than 2000 of them determine functions at the translational level miRNA-directed target degradation (MDTD) pathway of their target messengers 16,17 . In addition, new finding brought explanation for instability of some miRNAs, because the length of pairing with target could shorten the microRNA's life span 18,19 . miRNAs are degradated by cellular nucleases with pathway of target-directed miRNA degradation (TDMD) 20,21 .…”
Section: Micrornasmentioning
confidence: 99%